2016
DOI: 10.1039/c6nr01044j
|View full text |Cite
|
Sign up to set email alerts
|

Apoferritin fibers: a new template for 1D fluorescent hybrid nanostructures

Abstract: Recently, research in the field of protein amyloid fibers has gained great attention due to the use of these materials as nanoscale templates for the construction of functional hybrid materials. The formation of apoferritin amyloid-like protein fibers is demonstrated herein for the first time. The morphology, size and stiffness of these one-dimensional structures are comparable to the fibers formed by β-lactoglobulin, a protein frequently used as a model in the study of amyloid-like fibrillar proteins. Nanomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
(53 reference statements)
2
15
0
Order By: Relevance
“…Figure A shows an AFM image in which the quantum dots are clearly observed attached to the fiber. The labeling density is not homogeneous along the fiber, with some sections where the QDs seem to overlap, while others are not functionalized, consistent with previous observations using high‐resolution transmission electron microscopy (HR‐TEM) . The height of the QDs is about 8 nm and that of the fiber is slightly above 3 nm.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Figure A shows an AFM image in which the quantum dots are clearly observed attached to the fiber. The labeling density is not homogeneous along the fiber, with some sections where the QDs seem to overlap, while others are not functionalized, consistent with previous observations using high‐resolution transmission electron microscopy (HR‐TEM) . The height of the QDs is about 8 nm and that of the fiber is slightly above 3 nm.…”
supporting
confidence: 87%
“…In previous work, we showed that βLG can be readily functionalized with AlexaFluor 488 after amyloid‐like fiber formation to yield fluorescent fibers that appear homogeneously fluorescent at the spatial resolution provided by standard fluorescence microscopy . In the present study, correlative AFM and localization‐based super‐resolution fluorescence microscopy was used to gain information about the labeling properties at nanoscale spatial resolution both with dyes and QDs.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The 2D IR spectra exhibit the 1621 cm −1 peak and the corresponding cross peaks of amyloid β-sheets. Short amyloid morphologies are not uncommon and are observed in TEM images of other proteins with fibrillary, 41; 42 prefibrillar, 43; 44 oligomeric, 45 or amorphous morphologies. 46 These images and spectra are shown to illustrate the diversity in length that crystallin amyloids can adopt, as measured by TEM, and that 2D IR spectra exhibit characteristic amyloid β-sheet secondary structure even for lengths that are difficult to resolve with TEM.…”
Section: Resultsmentioning
confidence: 99%
“…The HsAFr surface can be modified with antibodies [14], peptides [15], aptamers [16] or small molecules such as folic acid (FA) [17]. Covalent modification of HsAFr lysine residues with the carboxyl functional group of targeting molecules can be used in the surface modification of HsAFr [18].…”
Section: Introductionmentioning
confidence: 99%